2017
DOI: 10.21873/anticanres.11740
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Recurrence Pattern of Far-advanced Gastric Cancer with Pathologicallypositive Para-aortic Lymph Nodes

Abstract: Abstract. Background: The role of para-aortic lymph node (PALN) dissection for far-advanced gastric cancer is controversial in patients with tumor diameter of ≥120 mm (HR=3.37;. Patients with none of these factors survived significantly longer than those with any of these factors respectively; p<0.001). Conclusion: Pathologically PALN-positive patients achieve long survival; however, the indications for PALN dissection should be carefully considered.Para-aortic lymph node (PALN) metastasis from gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…First, no more than 10% of patients have radiologically occult metastasis in the para-aortic region, which indicates that D2 resection is adequate for most patients. Meanwhile, the most common recurrence site is para-aortic region even after PAND [27,30]. In this study, patients who underwent D2 surgery had a 22.7% lymph node recurrence rate, which is comparable to the 24.6%-30.0% lymph node recurrence rate of patients who underwent D2 gastrectomy plus PAND in previous studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…First, no more than 10% of patients have radiologically occult metastasis in the para-aortic region, which indicates that D2 resection is adequate for most patients. Meanwhile, the most common recurrence site is para-aortic region even after PAND [27,30]. In this study, patients who underwent D2 surgery had a 22.7% lymph node recurrence rate, which is comparable to the 24.6%-30.0% lymph node recurrence rate of patients who underwent D2 gastrectomy plus PAND in previous studies.…”
Section: Discussionsupporting
confidence: 71%
“…Patients with a lower tumor burden or incurability de novo , which was characterized as a smaller tumor size, fewer metastatic lymph nodes, or fewer metastatic lymph node stations in gastric cancer with clinical PALM, are more prone to achieve CR of metastasis (Table 4); therefore, D2 gastrectomy was performed, resulting in a better prognosis. Kaito et al[27] found that involvement of a greater number of PAN stations was associated with a poorer prognosis. To date, most studies on surgical interventions in gastric cancer with clinical PALM have been limited to no more than two PAN stations (No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One problem in designing prospective trials of adjuvant RT is selecting patients who might have the highest chance to benefit from local control. Studies have identified many factors associated with loco-regional failure in univariate analysis, including tumour location [12], pT stage [7, 13, 14], pathologic node status [7, 13, 14], tumour grade [13], surgical margin status [15], extent of lymph node dissection [12, 15], and tumour size [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many predicting factors associated with LRR have been identified in previous studies, such as tumour location [12], pT stage [7, 13, 14], pathologic node status [7, 13, 14], extent of lymph node dissection [12, 15], tumour grade [13], and surgical margin status [15]. Considering these factors, postoperative adjuvant therapies and radiotherapy may be individualized to decrease recurrence rates, which will help to select suitable patients for radiotherapy in a multidisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%